A Fetus with Iniencephaly Delivered at the Third Trimester - Tanriverdi, Esra Cinar (Case Rep Med, 2015)
Iniencephaly is an uncommon neural tube defect, having retroflexion of the head without a neck and severe distortion of the spine. Iniencephaly is classified into two groups, iniencephaly apertus (with encephalocele) and iniencephaly clausus (without encephalocele). Incidence ranges from 0.1 to 10 in 10.000 pregnancies and it is seen more frequently in girls. Most of the fetuses with this defect die before birth or soon after birth, while those with the milder forms may live through childhood. Recurrence risk is around 1–5%. Family should be offered termination to reduce maternal risks and counseled for folic acid supplementation before the next planned pregnancy. Here we present a rare case of iniencephaly clausus which was diagnosed at 18th week of gestation by ultrasonography and delivered in the third trimester of pregnancy due to rejection of termination.